Quarterly economic review of USSR - Economist Intelligence Unit (Great Britain) (Economist Intelligence Unit Ltd., 1976)
Continues: QER: U.S.S.R..Split into: Country report. USSR, ISSN 0269-5480; Country profile. USSR.